Effects of climate warming and nitrogen deposition on subtropical montane ponds (central China) over the last two centuries: Evidence from subfossil chironomids. (July 2020) - Zheng, Ting; Cao, Yanmin; Peng, Jia; Bai, Xue; Chen, Xu
Abstract: Many remote montane ecosystems are experiencing biogeochemical changes driven by warming climate and atmospheric pollution. Compared with circumpolar and temperate lakes, the responses of subtropical montane lakes to these external stressors have been less investigated. Here we present sedimentary multi-proxies records (i.e. chironomids, elements and stable isotope of carbon and nitrogen) in 210 Pb-dated cores from two montane ponds (central China). Before the 1900s, low biomass and the dominance of opportunistic species (e.g. Chironomus anthracinus -type) in both ponds might be in response to cold and harsh condition. Thereafter, chironomid communities in both ponds experienced pronounced shifts. Nutrient-tolerant/warm-adapted species (e.g. Chironomus sp., Polypedilum nubeculosum -type and Endochironomus impar -type) proliferated and biomass increased synchronously after the 1900s, suggestive of favorable condition for chironomid growth. Redundancy analyses revealed that changes in chironomid communities in both ponds were significantly correlated with rising temperature and δ 15 N depletion. Prolonged growing season and nitrogen subsidy would increase primary productivity, and hence enhancing food availability for chironomids. Catchment-mediated indirect effects of warming and nitrogen deposition, such as hydrological changes and terrestrial organic matter inputs, would impose further influences on chironomid communities. Taken together, the combined effects of climate warming and nitrogen deposition have caused significant shifts in primary consumers of these montane ponds, and imposed cascading effects on structure and function of subtropical montane aquatic ecosystems. Graphical abstract: Image 1 Highlights: Chironomid and geochemistry records were retrieved from subtropical alpine ponds. Nutrient-tolerant/warm-adapted chironomid species proliferated after the 1900s. Shifts in chironomid communities were closely related to δ 15 N depletion and warming. Subtropical montane aquatic ecosystems are sensitive to warming and nitrogen input. Abstract : The main finding of the work: Climate warming and nitrogen deposition lead to shifts in chironomid communities of subtropical montane ponds.